2015
DOI: 10.1080/10408398.2013.876959
|View full text |Cite
|
Sign up to set email alerts
|

Omega 3 polyunsaturated fatty acids and the treatment of depression

Abstract: Depression is a common, recurrent, and debilitating illness that has become more prevalent over the past 100 years. This report reviews the etiology and pathophysiology of depression, and explores the role of omega 3 polyunsaturated fatty acids (n-3 PUFA) as a possible treatment. In seeking to understand depression, genetic factors and environmental influences have been extensively investigated. Research has led to several hypotheses for the pathophysiological basis of depression but a definitive pathogenic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(68 citation statements)
references
References 119 publications
2
65
0
1
Order By: Relevance
“…Tsuboi et al (2013) [7] reported that increased levels of serum saturated fatty acids and ω-6 PUFAs such as arachidonic acid (AA, C22:4, ω-6), are associated with depression. On the contrary, ω-3 PUFAs are involved in the attenuation of neuro-inflammation [8], prevention of neuronal death [9], and development of cognitive ability [10,11] and improvement of mood disorders in humans and animals [12][13][14]. These reports support the concept that brain inflammation, depression, and anxiety seen in patients suffering from mental disorders may be related to a deficiency in ω-3 PUFAs.…”
Section: Introductionmentioning
confidence: 62%
“…Tsuboi et al (2013) [7] reported that increased levels of serum saturated fatty acids and ω-6 PUFAs such as arachidonic acid (AA, C22:4, ω-6), are associated with depression. On the contrary, ω-3 PUFAs are involved in the attenuation of neuro-inflammation [8], prevention of neuronal death [9], and development of cognitive ability [10,11] and improvement of mood disorders in humans and animals [12][13][14]. These reports support the concept that brain inflammation, depression, and anxiety seen in patients suffering from mental disorders may be related to a deficiency in ω-3 PUFAs.…”
Section: Introductionmentioning
confidence: 62%
“…A recent review by Deacon et al 41 formed variable conclusions by systematic review and meta-analysis. Results from the research done on the effects of omega-polyunsaturated fatty acids on the depression related mood disorder have led to variable results 41 .…”
Section: More Recent Insights On Omega-3 Fatty Acids and Depressionmentioning
confidence: 99%
“…Results from the research done on the effects of omega-polyunsaturated fatty acids on the depression related mood disorder have led to variable results 41 . Furthermore as the findings from various research studies about omega-3 fatty acids and the treatment of depression are conflicted.…”
Section: More Recent Insights On Omega-3 Fatty Acids and Depressionmentioning
confidence: 99%
“…Fatty acids, and especially the omega-3 long-chain polyunsaturated fatty acids ( n -3 LCPUFA), are being researched extensively for a wide array of health outcomes varying from, but not exclusive to, cardiovascular diseases, depression and cognition [1,2,3]. As in every health related field, randomized controlled supplementation trials are the gold standard to demonstrate efficacy of n -3 LCPUFA [4].…”
Section: Introductionmentioning
confidence: 99%